UTILIZATION OF TECHNOLOGY AS A MATHEMATICS LEARNING MEDIA TO SUPPORT LEARNING IN SCHOOLS - Windra; Baso Intang Sappaile (International Journal of Teaching and Learning, 2025)
This literature research discusses the use of technology as a mathematics learning medium to support the learning process in schools. Modern technologies such as Augmented Reality (AR), Virtual Reality (VR), and Artificial Intelligence (AI) have shown their potential in changing the way teachers and students interact with mathematical material. The use of this technology allows the application of more interactive, personalized and collaborative learning methods, which leads to increased student understanding and motivation. This study examines several important aspects in the application of technology to mathematics learning, including how the technology facilitates the visualization of complex mathematical concepts, offers personalized assistance according to student needs, and encourages collaboration between students. The results obtained show that the integration of technology in mathematics learning can increase the effectiveness and efficiency of the teaching and learning process, thereby creating an adaptive and innovative educational environment. Thus, the use of technology as a medium for mathematics learning is a strategic step in the modernization of education that contributes positively to improving the quality of students' learning experiences. This research recommendation focuses on further development and training for educators in utilizing technology optimally to support learning in schools.